RETRACTED: Komputer Interaktif sebagai Media Pengajaran Bahasa Inggris pada Anak Usia Dini - Putri Asilestari (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2016)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini to article entitled Komputer Interaktif sebagai Media Pengajaran Bahasa Inggris pada Anak Usia Dini Vol 2, No 1, pp. 55-62, June 2016, This paper has been found to be in violation of the Jurnal EDIMAS VOL 6 NO 1 TAHUN 2015. Title: KOMPUTER INTERAKTIF SEBAGAI MEDIA PENGAJARAN BAHASA INGGRIS PADA ANAK USIA DINI. Authors: Arso Setyaji, Ahmad Iskak, Rahmawati Sukmaningrum, Faiza Hawa. DOI: https://doi.org/10.26877/e-dimas.v6i1.794 Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Jurnal EDIMAS VOL 6 NO 1 TAHUN 2015 The document and its content has been removed from Jurnal PAUD Tambusai, and reasonable effort should be made to remove all references to this article.